Analisis Kompetensi dan Budaya Kerja terhadap Kinerja Di Era Reformasi 4.0 - Panggabean, Romli Jumpai; Ahman, Eeng; Disman, Disman; Rofaida, Rofi (Image : Jurnal Riset Manajemen, 2023)
The purpose of this research to determine the effect of competency and work culture on employee performance in the reform era 4.0 at Bank Sahabat Sampoerna Operational Division. The method in this research is quantitative descriptive through multiple linear regression analysis with the help of the SPSS version 26 program. The results show that competency partially has a positive and significant effect on employee performance, work culture partially has a positive and significant effect on employee performance, competency and work culture simultaneously have a positive and significant effect on employee performance. The implication of these findings suggests that investing in enhancing employee competencies and fostering a conducive work culture can lead to improved performance within the Bank Sahabat Sampoerna Operational Division. Moreover, the simultaneous positive effects of competency and work culture highlight the importance of addressing both factors in the reform era 4.0 to maximize employee performance effectively.